Government Policy about the Integration of General Science and Religion at the Senior High School/Madrasah Aliyah - R Rahmatullah (TARBIYA: Journal of Education in Muslim Society, 2016)
Abstract The research problem was how to extent government policy about the integration of general science and religion at the Senior High School/ Islamic Senior High School. The objective of the research was to know the factor of the government policy about the integration of general science and religion, its background, destination, contents, implementation, obstacle and solution of government policy at the Senior High School/Islamic Senior High School, DKI Jakarta. The method of research used was documentation, history and triangulation methods. The finding of research was to integrate general science and religion at Senior High School/Islamic Senior High School, its limited the justification of Qur’an verses only, not to the real science of Islamization. Abstrak Masalah penelitian ini adalah bagaimana meningkatkan kebijakan pemerintah tentang integrasi ilmu umum dan agama di SMA / Madrasah Aliyah. Tujuan penelitian ini adalah untuk mengetahui faktor kebijakan pemerintah tentang integrasi ilmu pengetahuan umum dan agama, latar belakang, tujuan, isi, pelaksanaan, hambatan dan solusi atas kebijakan pemerintah di SMA / Madrasah Aliyah di DKI Jakarta. Metode penelitian yang digunakan adalah metode dokumentasi, sejarah dan triangulasi. Temuan dari penelitian ini adalah bahwa untuk mengintegrasikan ilmu umum dan agama di SMA / Madrasah Aliyah hanya terbatas pada pembenaran ayat-ayat Qur'an saja, bukan ilmu-ilmu Islam yang sebenarnya. How to Cite : Rahmatullah. Tafsir, A. Mujahidin, E. (2016). Integrating Science and Religion: An Analysis on The Policy of The Government at Senior High School/Madrasah Aliyah. TARBIYA: Journal Of Education In Muslim Society, 3(1), 32-50. doi:10.15408/tjems.v3i1. 3408. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i1. 3408